Towards Sustainable Renewable Energy Investment and Deployment - United Nations Economic Commission for Europe (United Nations, 2021)
This toolkit for renewable energy policy-makers and investors builds on the work already done by the United Nations Economic Commission for Europe (ECE) towards sustainably increasing renewable energy investments and improving cross-sectoral planning in decision-making processes. The Renewable Energy Hard Talk events held in Bosnia and Herzegovina (2018) and Serbia (2019) included a Nexus component for this purpose. Substantively, the approach used drew from the nexus assessment work under the ECE Water Convention and evolved into a list of criteria for sustainable renewable energy policies and investment initiatives that bring multiple benefits across sectors and countries while minimizing trade-offs, including with other water uses and environment protection.